OGT Mediated Histone H2B S112 GlcNAcylation Regulates DNA Damage Response. Issue 9 (20th September 2015) - Wang, Panfei; Peng, Changmin; Liu, Xia; Liu, Hailong; Chen, Yali; Zheng, Li; Han, Baolin; Pei, Huadong
Abstract O-GlcNAcylation is an important post-translational modification and has been implicated in many fundamental cellular processes. Recent studies showed that O-linked N-acetylglucosamine (GlcNAc) transferase (OGT) mediated O-GlcNAcylation of histone H2B Ser 112 (H2B S112 GlcNAcylation) plays an important role in gene transcription. However, the role of this histone modification in DNA damage response has not been studied yet. In this study, we found that OGT and OGT mediated H2B S112 GlcNAcylation are involved in DNA damage response for maintaining genomic stability and are required for resistance to many DNA-damaging and replication stress-inducing agents. OGT mediated H2B S112 GlcNAcylation increased locally upon the induction of double-strand breaks (DSBs), and depletion of OGT or overexpression of H2B S112A mutant impaired homologous recombination (HR) and nonhomologous end-joining (NHEJ). Mechanistically, H2B S112 GlcNAcylation could bind Nijmegen breakage syndrome 1 (NBS1) and regulate NBS1 foci formation. Taken together, our results demonstrate a new function of histone O-GlcNAcylation in DNA damage response (DDR).